Displaced clines in an avian hybrid zone (Thamnophilidae: Rhegmatorhina) within an Amazonian interfluve*. (22nd October 2021) - Del‐Rio, Glaucia; Rego, Marco A.; Whitney, Bret M.; Schunck, Fabio; Silveira, Luís F.; Faircloth, Brant C.; Brumfield, Robb T.
Abstract: Secondary contact between species often results in the formation of a hybrid zone, with the eventual fates of the hybridizing species dependent on evolutionary and ecological forces. We examine this process in the Amazon Basin by conducting the first genomic and phenotypic characterization of the hybrid zone formed after secondary contact between two obligate army‐ant‐followers: the White‐breasted Antbird ( Rhegmatorhina hoffmannsi ) and the Harlequin Antbird ( Rhegmatorhina berlepschi ). We found a major geographic displacement (∼120 km) between the mitochondrial and nuclear clines, and we explore potential hypotheses for the displacement, including sampling error, genetic drift, and asymmetric cytonuclear incompatibilities. We cannot exclude roles for sampling error and genetic drift in contributing to the discordance; however, the data suggest expansion and unidirectional introgression of hoffmannsi into the distribution of berlepschi .